A new genus and four new species of subfamily Cyclocypridinae (Crustacea, Ostracoda) from Thailand - Savatenalinton, Sukonthip (Zootaxa, 2017)
A new genus, Dentocypria n. gen., in the subfamily Cyclocypridinae Kaufmann, 1900 is described from Thailand. The main distinguishing characters of the new genus are the presence of an internal tooth on the antero-ventral part of the left valve, the marginal tubercles on the right valve, the very elongated terminal segment of the madibular palp, the absence of setae on the basal segment of the second thoracopod (T2), the unusually long e-seta of T2, the short terminal segment of the third thoracopod (T3), the long Sp seta of the caudal ramus and the morphology of prehensile palps and hemipenis. Four new species of the new genus are here described: Dentocypria mesquitai n. gen. n. sp., Dentocypria chantaranothaii n. gen. n. sp., Dentocypria smithi n. gen. n. sp. and Dentocypria aequiloba n. gen. n. sp. A brief discussion on the generic characters and a key to the genera of the subfamily are provided.